Wheelchair basketball quantification - Gil-Agudo, A.; del Ama-Espinosa, A.; Crespo-Ruiz, B. (Physical Medicine & Rehabilitation Clinics of North America, 2010)
Classification systems are one of the key elements in sports for people with disability, including wheelchair basketball. Further scientific studies to validate classification systems are needed. This article describes the most relevant research, with emphasis on biomechanics.